State Responsibility Toward Announced Children In Government Operations In The Field Of Children's rights protection - Realizhar Adillah Kharisma Ramadhan (International Journal of Education, Vocational and Social Science, 2024)
The idea of good governance has not been institutionalized in the government system, and the government does not have a strong desire to care for abandoned children, which contributes to the lack of realization of the state's responsibility towards neglected children in government operations. In addition, there are other challenges that frequently arise when attempting to defend the rights of Indonesian children, particularly those who have been neglected. These challenges include: the application of law enforcement itself, which pertains to the ability of law enforcement officials; infrastructure and supporting facilities; and the ineffective implementation of certain government programs. Taking into account that the majority of Indonesians still have low levels of economic capacity, that the public, particularly parents, are unaware of children's rights, that relevant agencies and the general public do not understand the provisions of the International Convention on the Rights of the Child, that there is a dearth of coordination between governments and social organizations, and that cross-sectoral and international cooperation is not well established.